Free vibration of laminated composite plates with a hole and a delaminated hole - Lim, Jonathan Zhen-Yang. (2011)
This report explores the aspect of vibration testing of Carbon Fiber Reinforced Polymer (CFRP) composite laminates. The test specimens were square composite plates that consisted of eight layers unidirectional layup. The aim is to study the natural frequency of these composite specimens across various mode numbers and to investigate the effects of the composite square plates in terms of hole cutout, delamination size and delamination location. CFRP square specimens with various parameters such as different hole sizes and delamination areas are observed.